A Systematic Literature Review on Value Co-Creation and the Technology Acceptance Model (TAM) for E-Book Adoption in Educational Settings - Wijoyo, Agung; Aspiranti, Tasya; Nurhayati, Nunung; Amaliah, Ima; Lestari, Rini (Yayasan Gema Bina Nusantara, 2025)
The advancement of digital technologies has significantly reshaped educational practices, positioning e-books as essential tools in contemporary learning environments. Despite their potential, the actual adoption of e-books by educators remains uneven, particularly in secondary education. This study presents a systematic literature review that integrates the Technology Acceptance Model (TAM) with Value Co-Creation (VCC) to explain the dynamics of e-book adoption among teachers. By synthesizing recent scholarly contributions, the review identifies VCC as a strategic antecedent that enhances TAM constructs Perceived Usefulness (PU) and Perceived Ease of Use (PEOU) through participatory design, collaborative implementation, and feedback-driven development. The findings reveal that co-creation fosters psychological ownership, reduces technology anxiety, and strengthens behavioral intention and actual use of e-books. Furthermore, collaborative strategies improve the pedagogical relevance and usability of digital platforms, making them more aligned with instructional needs. This paper proposes an integrated conceptual framework that positions VCC as a catalyst for technology acceptance, offering practical insights for educational leaders, policymakers, and developers seeking to accelerate digital transformation in schools. The study contributes to the literature by bridging managerial and psychological perspectives, emphasizing the importance of inclusive, value-driven innovation in education.